UK Government launches new £1.9bn cyber-security strategy. Issue 11 (November 2016) - Unknown
Abstract : The 'National Cyber Security Strategy 2016 to 2021' recently unveiled by the UK Government outlines how it will use a £1.9bn investment in cyber-defences to protect UK businesses.